Implementation of Management Functions in the Development of Da'wah Programs in Islamic Community Organizations in North Sumatra - Damayanti, Maya Dewi; Sahputra, Dika (Analisis: Jurnal Studi Keislaman, 2025)
EEffective management of da'wah programs requires a structured and systematic approach so that the desired goals can be achieved optimally. Therefore, the application of appropriate management principles in every aspect of da'wah activities is very important. The application of da'wah management plays a crucial role in directing and ensuring that da'wah activities are carried out professionally. Every da'wah activity needs to be designed, planned, organized, and evaluated carefully to achieve maximum results. This study uses a qualitative descriptive approach with a case study design. Data were collected through interviews with informants, observation, and documentation. Data processing and analysis were carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that at the planning stage, PWNU planned long and short terms through coordination meetings, PWM used an activity timeline, and PW Al-Washliyah relied on the da'wah syllabus. In organizing, each organization has a clear and organized management structure. At the implementation stage, the three organizations focused on motivation and effective communication to encourage member participation. In controlling, the three organizations carried out periodic supervision to ensure the smooth running of the program. Overall, this study shows a high commitment from the three organizations in implementing da’wah management in a structured, organized and measurable manner in order to achieve maximum da’wah goals.